"I have a personal claim to myself": a visually impaired student's perspective on her participation in physical activity and physical education settings - Anne Bödicker; Sandra Elisath (Frontiers in Sports and Active Living)
In our daily lives, we often come across ideas and approaches that are intended to support and enhance our well-being, with the aim of achieving positive results, such as resilience and health, if implemented effectively. This trend can be understood as part of the long history of disciplining and normalizing the body in Western societies. Functioning, keeping up, and being resilient in our fast-paced society now appear to be the social norm. This status quo creates a link to physical education (PE) as a body-related school subject, where the focus is on the body and its performance. Several recent studies have explored the experiences of people with visual impairment (VI) in PE. For young people with blindness and visual impairment (BVI), sports and physical activity (PA) are deemed beneficial as they promote physical and mental health while increasing well-being and life satisfaction. These factors—well-being and life satisfaction—are closely intertwined with the concept of resilience. However, resilience cannot be conceived without acknowledging vulnerability, which people embody to different degrees. Vulnerability represents a human condition, as all people are potentially vulnerable. What can this concept mean for adolescents who are assigned to a so-called vulnerable group? This article aims to explore this question from a biography-oriented perspective. By adopting a critical perspective of Ableism within the context of Disability Studies, we reclassified societal attributions of abilities. This article focuses on a semi-narrative guided interview conducted with a 15-year-old teenager with BVI who had recently transitioned from inclusive mainstream schools to a state-approved special school for the visually impaired. Thus, she has had diverse experiences in both segregated and inclusive educational settings. This study highlights the extent to which empowering personal and non-personal factors are perceived as such and examines their interaction with participation in sports contexts. The findings critically reflect on the teachers' role in either enabling or hindering participation in PE, emphasizing the need for inclusion-sensitive approaches in teacher education.